Factors Affecting Infant Feeding Practices Among Women With Severe Mental Illness - Baker, Natasha; Potts, Laura; Jennings, Stacey; Trevillion, Kylee; Howard, Louise M. (Frontiers in Global Women's Health, 2021)
Background The health benefits of breastfeeding are well established but for mothers with severe mental illness (SMI), the decision to breastfeed can be complex. Very few prior studies have investigated the infant feeding choices of women with SMI, or factors associated with this. We aimed to examine antenatal infant feeding intentions and outcomes in a cohort of women admitted for acute psychiatric care in the first postpartum year. We also aimed to examine whether demographic and clinical characteristics associated with breastfeeding were similar to those found in previous studies in the general population, including age, income, education, BMI, mode of delivery, smoking status, and social support. Methods This study was a mixed-methods secondary analysis of a national cohort study, ESMI-MBU (Examining the effectiveness and cost-effectiveness of perinatal mental health services). Participants had been admitted to acute care with SMI in the postpartum. Infant feeding outcomes were retrospectively self-reported by women during a one-month post-discharge interview. Free-text responses to questions were also explored using thematic analysis. Results 144 (66.1%) of 218 women reported breastfeeding. 85% of the cohort had intended to breastfeed and of these, 76.5% did so. Factors associated with breastfeeding included infant feeding intentions, employment, non-Caucasian ethnicity and being in relationship/married. Although very few women were taking psychotropic medication contraindicated for breastfeeding, over a quarter (n= 57, 26.15%) reported being advised against breastfeeding because of their medication. Women were given this advice by psychiatry practitioners (40% n= 22), maternity practitioners (32.73% n=18) and postnatal primary care (27.27% n=15). Most women stopped breastfeeding as a result (81.1% n= 43). 25 women provided free text responses, most felt unsupported with infant feeding due to inconsistent information about medication when breastfeeding and that breastfeeding intentions were de-prioritised for mental health care. Conclusion Women with SMI intend to breastfeed and for the majority, this intention is fulfilled. Contradictory advice relating to breastfeeding and psychotropic medication indicates that care provider training is required about how to manage infant feeding in this population. Further research is required to develop a more in-depth understanding of the unique infant feeding support needs of women with perinatal SMI.